"The New Costumes of Odd Sizes": Plus-Sized Women's Fashions, 1920–1929. (October 2013) - Keist, Carmen N.; Marcketti, Sara B.
By 1916 over 13 million women or 12.7% of the total U.S. population was considered overweight or "stout." In the 1920s, the term "stout." indicated an (often matronly appearance) with generous bust, back and hip curves that did not fit with fashion s demands of the ideal stylish figure. Research related to ready-to-wear fashions for plus sized women in the 20th century is almost non-existent. The purpose of this study was to explore available ready-to-wear fashions for the plus sized woman during the years 1920-1929. To explore this topic, a historical method approach was utilized using primary sources that included The New York Times, Vogue, and Good Housekeeping . The results of this study identified prescriptive and proscriptive advice regarding appropriate clothing styles and merchandising trends marketed to plus sized women.